The paternal genetic legacy of Hungarian-speaking Rétköz (Hungary) and Váh valley (Slovakia) populations - Pamjav, Horolma; Fóthi, Ábel; Dudás, Dániel; Tapasztó, Attila; Krizsik, Virág; Fóthi, Erzsébet (Frontiers in Genetics, 2022)
One hundred and six Rétköz and 48 Váh valley samples were collected from the contact zones of Hungarian-Slovakian territories and were genotyped for Y-chromosomal haplotypes and haplogroups. The results were compared with contemporary and archaic data from published sources. The genetic composition of the Rétköz population from Hungary and the Váh Valley population from Slovakia indicates different histories. In the Rétköz population, the paternal lineages that were also found in the Hungarian Conquerors, such as R1a-Z93, N-M46, Q-M242, and R1b-L23, were better preserved. These haplogroups occurred in 10% of the population. The population of the Váh valley, however, is characterized by the complete absence of these haplogroups. Our study did not detect a genetic link between the Váh Valley population and the Hungarian Conquerors; the genetic composition of the Váh Valley population is similar to that of the surrounding Indo-European populations. The Hungarian Rétköz males shared common haplotypes with ancient Xiongnu, ancient Avar, Caucasian Avar, Abkhazian, Balkarian, and Circassian males within haplogroups R1a-Z93, N1c-M46, and R1b-L23, indicating a common genetic footprint. Another difference between the two studied Hungarian populations can be concluded from the Fst-based MDS plot. The Váh Valley, in the western part of the Hungarian-Slovakian contact zone, is genetically closer to the Western Europeans. In contrast, Rétköz is in the eastern part of that zone and therefore closer to the Eastern Europeans.